Protein adjustments in heat stressed finishing cattle - D.R. Ames; C.L. Willms (Kansas Agricultural Experiment Station Research Reports, 1977)
A summer feedlot trial indicates that protein can be removed from finishing rations in proportion to magnitude of heat stress without causing a decline in average daily lain. Cattle consumed .13 kg/hd/day (.30 lb) less supplemental protein soybean oil meal) during the 82-day period with no decline in average daily gain when compared to controls.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen' s Day; 1977; Beef; Protein; Heat stress; Finishing cattle